The Collapse of the SVD Togo Mission (1914-1921) - Miotk, Andrzej (Annales Missiologici Posnanienses, 2016)
This case-study is a study of the three stages of “The Collapse of the SVD Togo Mission (1914-1921)”: the Anglo-French Occupation (1914-1917); the Expulsion and Internment of the SVD Missionaries (1917-1918) and the Definitive Loss of the SVD Togo Mission (1918-1921). The investigation, based on archival sources of the SVD Generalate Archives in Rome (AG SVD) traced the unfolding of events within the international efforts to save the mission in the thriving Protectorate of Togo. The collapse of the SVD Togo Mission driven by rampant nationalism was brought about by the expulsion of its 53 missionaries in seven groups within three months. Even if the expelled German missionaries were pervaded by a deep spirit of patriotism, they were first and foremost religiously motivated men. In the end, they wound up as victims of the political entanglements. The Treaty of Versailles deprived the missions of significant apostolic forces. More than 1,000 German missionaries, including 130 Divine Word Missionaries, were thus excluded from mission territories as victims of political calculations. The SVD missionaries were released from internment within the year due to the urgent actions of their Superior General, Fr. Nikolaus Blum. They accepted the course of events in a truly apostolic spirit and received new assignments, mainly to the Dutch East Indies (Indonesia).